NILAI ESTETIS DAN â€œDULCE ET UTILEâ€ DALAM NOVEL KEINDAHAN DAN KESEDIHAN KARYA KAWABATA YASUNARI - Novi Andari (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2013)
Abstract. This article is exploring the aesthetical aspects of Yasunari’s novel Keindahan dan Kesedihan. Aesthetic aspects applied here are in accordance with those of Horace, that is dulce et utile. Through analyzing these aspects, one may come to the judgment whether a literary work is a great work or not. The result of analysis shows that Yasunari’s Keindahan dan Kesedihan applies a good quality of dulce et utile. It can be sense in the existence of the unity in variety, disinterested contemplation, aesthetic distance, framing, invention, and creation and one may read the use of selected dictions and may gain values from reading the novel. Key words : aesthetic value, dulce et utile, aesthetic distance, framing